Financial Literacy and Financial Well-Being among Working Professionals in Dolakha District - Utsab Pokharel (Journal of Corporate Finance Management and Banking System, 2024)
The study attempts to examine the influence of financial literacy on financial well-being, the purpose of study is to identify the most influencing factors of financial literacy on financial well-being and analyze the mediating role of financial self-efficacy on working professionals. The causal comparative research design was employed in the investigate the cause and effect of financial literacy on financial well-being. Data gathered from 229 respondents through structured questionnaires distributed via KOBO toolbox utilized convenience sampling. Quantitative analysis involved both descriptive and inferential statistics, employing the PLS-SEM method. Out of four determinants of financial literacy determinants considered for the study, financial attitude, financial experience, financial skills had significant impact on financial self-efficacy however, financial awareness did not have a significant impact. Further, the study results found that financial self-efficacy had a significant impact on financial well-being of working professionals in Dolakha district. The results establish the mediating role of financial self-efficacy. This study is limited to current and potential working professionals in Dolakha district, utilizing cross-sectional data, which may restrict generalizability. Nevertheless, the outcome of the study will assist all the stakeholders, including employers, policymakers, local governments in Dolakha district. The application of this study is extensive. The study’s findings will assist policymakers, local governments, employers and financial literacy researchers all stakeholder to protect the financial well-being of working professionals in Dolakha district. Similarly, improving the financial well-being of working professionals from rural part of Nepal can help reducing poverty by encouraging investing and fair economic growth. To the best of the author’s knowledge, this study is one of the earliest studies to financial literacy and financial well-being a study on working professionals in Dolakha district by using PLS-SEM and theory of planned behavior.